1983
DOI: 10.1001/jama.250.15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Maternal birth weight and subsequent pregnancy outcome

Abstract: The relationship between maternal birth weight and future reproductive outcome was studied in a cohort of 748 white women with singleton pregnancies. Maternal birth weight was significantly related to stature, prepregnancy weight, pregnancy weight gain, baby's birth weight, gestational duration, relative intrauterine growth, the baby's need for neonatal intensive care, transient tachypnea of the newborn, and idiopathic respiratory distress syndrome. Mothers who weighted 2,000 g or less at birth were at elevate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0
9

Year Published

1987
1987
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 0 publications
5
38
0
9
Order By: Relevance
“…The latter is a potentially deadly condition. Hackman et al (1983) find an inverse association between the mother's birth weight and the baby's need for intensive care. See also the surveys by Lummaa (2003) and Sloboda et al (2011).…”
Section: Estimation Results By Gendermentioning
confidence: 80%
“…The latter is a potentially deadly condition. Hackman et al (1983) find an inverse association between the mother's birth weight and the baby's need for intensive care. See also the surveys by Lummaa (2003) and Sloboda et al (2011).…”
Section: Estimation Results By Gendermentioning
confidence: 80%
“…development, may influence her later reproductive performance (Hackman et al, 1983;Emanuel, 1986). Indeed, one British study demonstrated that a mother's own birth weight (which is an indicator of her own intrauterine growth and development) may be of paramount importance in determining her own babies' development in utero (Ounsted and Ounsted, 1966).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that birth weights of mothers are related to those of their own children and even their children's children (Hackman et al, 1983;Klebanoff et al, 1984). Women who were themselves small-for-gestational age (SGA) are twice at risk of having an SGA baby themselves (Klebanoff et al, 1989;Skjaerven et al, 1997) as well as being at a greater risk of developing adulthood diseases such as noninsulin-dependent diabetes mellitus (NIDDM) and hypertension (Phillips, 1996 and1998).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the legal and ethical restrictions on the use of human subjects in scientific research, empirical evidence on the relationship between prenatal malnutrition and subsequent reproductive function has mainly been derived from observational studies. A number of such studies showed that women's prenatal conditions, as measured by their birth weight, are negatively associated with their subsequent risk of foetal loss and preterm birth, and positively associated with babies' birth weight and chance of survival (Emanuel et al 1992;Hackman et al 1983;Klebanoff, Meirik, and Berendes 1989;Little 1987;Sanderson, Emanuel, and Holt 1995;Skjaerven, Wilcox, and Magnus 1997). However, due to the weaknesses of observational design, the causal nature of these findings remains unclear.…”
Section: Introductionmentioning
confidence: 99%